THE RELATIONSHIP LEVEL OF KNOWLEDGE WITH CLEAN AND HEALTHY LIFESTYLE (PHBS) HOUSEHOLDS IN BURBIAH VILLAGE, CENTRAL ACEH DISTRICT - Adinda Agustia Rinaldi; M. Iqbal Fahlevi (RADJA PUBLIKA, 2023)
Clean and Healthy Living Behavior (PHBS) are all health behaviors that are carried out consciously so that family members or families can help themselves in the health sector and play an active role in health activities in the community. The research aims to determine the relationship between the level of knowledge and household PHBS in the community in Burbiah Village. The method used in this study is descriptive analytics with a cross sectional approach. This research was conducted through primary data collection from the Burbiah Village community and secondary data collection from the Central Aceh District Health Office and the Bebesen Health Center. Based on the results of research on the relationship between the level of knowledge and the clean and healthy lifestyle of households in Burbiah Village, it shows that there is a relationship between the level of knowledge and the clean and healthy behavior of households. Shown with a significant 0.000 with a positive relationship direction of 0.958 so that it shows a perfect relationship between the level of knowledge and household clean and healthy living behavior. It was concluded that there is a relationship between the level of knowledge and clean and healthy living behavior in Burbiah Village, Bebesen District, Central Aceh District, namely there is a positive relationship between the level of knowledge of respondents and household clean and healthy living behavior. 958 so that it shows a perfect relationship between the level of knowledge and the behavior of a clean and healthy household life. It was concluded that there is a relationship between the level of knowledge and clean and healthy living behavior in Burbiah Village, Bebesen District, Central Aceh District, namely there is a positive relationship between the level of knowledge of respondents and household clean and healthy living behavior. 958 so that it shows a perfect relationship between the level of knowledge and the behavior of a clean and healthy household life. It was concluded that there is a relationship between the level of knowledge and clean and healthy living behavior in Burbiah Village, Bebesen District, Central Aceh District, namely there is a positive relationship between the level of knowledge of respondents and household clean and healthy living behavior.